Alkane determination of sediment core IDLE-TOW10-9B rom Lake Towuti in Sulawesi, Indonesia - Parish, Meredith; Russell, James M; Konecky, Bronwen; Du, Xiaojing; He, Chengfei; Bijaksana, Satria; Vogel, Hendrik (PANGAEA, 2024)
We produced leaf wax hydrogen and carbon records from the Lake Towuti, spanning the last deglaciation. We measure hydrogen isotopes in 55 samples in the past 30 ka, and measured carbon isotopes at half the resolution.
Keywords: alkanes; Carbon; deglacial; Deglaciation; hydroclimate; hydrogen; Indonesia; Indo-Pacific Warm Pool; Last Glacial Maximum; Leaf wax; LGM; Maritime Continent; precipitation; Warm Pool